2019
DOI: 10.4236/jep.2019.107056
|View full text |Cite
|
Sign up to set email alerts
|

Health Risk Assessment of Heavy Metals and Microbial Quality of Local Tomato (<i>Solanum lycopersicum</i>) of Ouagadougou, Burkina Faso

Abstract: Tomato fruit enormously consumed in Burkina Faso is a source of health risk due to its quality. The plant of tomato cultivated in most the industrially polluted area as Ouagadougou, accumulates significant quantities of heavy metals and microorganisms and could be dangerous for consumption. The present study was conducted to investigate heavy metal and microbial contamination in soils wastewater and vegetables (tomato fruit) and to evaluate the possible health risks associated with the consumption of vegetable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…fresh weight to dry weight of vegetables (0.085)[37] [38], IR is the daily intake rate of native potato from tubers (kg/day/person). According to the questionnaire carried out in the four localities, the average daily intake of native potatoes between "peruanita" and "huayro macho" potatoes was 165.1 ± 59.1 g/day for children and 468.4 ± 126.7 g/day for adults.…”
mentioning
confidence: 99%
“…fresh weight to dry weight of vegetables (0.085)[37] [38], IR is the daily intake rate of native potato from tubers (kg/day/person). According to the questionnaire carried out in the four localities, the average daily intake of native potatoes between "peruanita" and "huayro macho" potatoes was 165.1 ± 59.1 g/day for children and 468.4 ± 126.7 g/day for adults.…”
mentioning
confidence: 99%
“…Various studies on the microbiological quality of fresh tomatoes have identified a wide range of microorganisms of potential public health risks. Among the pathogens that have been identified, Staphylococcus, Salmonella and E. coli are the most frequently reported microbial hazards from tomato VCs globally (Ogundipe et al, 2012;Julien et al, 2017;Sahile and Teshome, 2019;Somda et al, 2019;Younus et al, 2020). Though detection of bacteria species from tomato samples does not necessarily imply food safety problems, various studies from Ethiopia have also reported the occurrence of coliforms, E. coli, Salmonella spp; Staphylococcus, Klebsiella spp, Shigella; Pseudomonas, Proteus in fresh tomatoes (Ashenafi, 1989;Dugassa et al, 2014;Alemu et al, 2018;Sahile and Teshome, 2019;Degaga et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…For vegetable production, tomatoes (Solanum lycopersicum) are second main produced vegetable after onion bulbs (Allium cepa) and generate significant financial resources for the national economy [2]. National tomato production is estimated at 157,086 tons per year and remains the most profitable vegetable crop in the country with total sales valued at 117 million euros [3].…”
Section: Introductionmentioning
confidence: 99%